2016
DOI: 10.1155/2016/5314312
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Maintenance Optimization in Healthcare Domain: Status of Research and Perspective

Abstract: Although medical equipment maintenance has been carefully managed for years, very few in-depth studies have been conducted to evaluate the effectiveness and efficiency of these implemented preventive maintenance strategies, especially after the debate about the credibility of manufacturer's recommendations has increased in the clinical engineering community. Facing the dilemma of merely following manufactures maintenance manual or establishing an evidence-based maintenance, medical equipment maintenance could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
(83 reference statements)
0
22
0
Order By: Relevance
“…Swamidas et al (2018) further apply Fault Tree Analysis for identifying root causes of unsafe dosage rates for brachytherapy, a form of radiotherapy used for treating certain forms of cancer, such as cervical and prostate. Application of Fault Tree Analysis for clinical risk factors affecting patient safety is discussed in several studies, including assessing safety of anesthesia (Liu and Yuan 2015;Culwick et al 2016), maintenance-related hazards of medical devices (Mahfoud et al 2016;García et al 2019;Labagnara et al 2013) or assessing risk profiles of programs for stereotactic radiosurgery (Teixeira et al 2016). More recent applications of Fault Tree Analysis for dialysis treatment is discussed for management of medical waste (Makajic-Nikolic et al 2016), and assessing hazards of hemodialysis devices, (Leupolz et al 2018).…”
Section: Concepts and Methodologies For Risk Assessment In Health Carementioning
confidence: 99%
“…Swamidas et al (2018) further apply Fault Tree Analysis for identifying root causes of unsafe dosage rates for brachytherapy, a form of radiotherapy used for treating certain forms of cancer, such as cervical and prostate. Application of Fault Tree Analysis for clinical risk factors affecting patient safety is discussed in several studies, including assessing safety of anesthesia (Liu and Yuan 2015;Culwick et al 2016), maintenance-related hazards of medical devices (Mahfoud et al 2016;García et al 2019;Labagnara et al 2013) or assessing risk profiles of programs for stereotactic radiosurgery (Teixeira et al 2016). More recent applications of Fault Tree Analysis for dialysis treatment is discussed for management of medical waste (Makajic-Nikolic et al 2016), and assessing hazards of hemodialysis devices, (Leupolz et al 2018).…”
Section: Concepts and Methodologies For Risk Assessment In Health Carementioning
confidence: 99%
“…The overall goal of the maintenance procedures is to raise the overall equipment effectiveness. Evidence in the literature points that mathematical modeling is much more flexible than empirical approaches, and medical maintenance would benefit from optimization modeling [25]. Khalaf et al [26,27] proposed a mathematical model that adopted a mixed integer based approach maintenance scheduling technique a software maintainability for maintenance predication purposes was formulated based on both experience in software architecture development and haemodialysis machine architecture.…”
Section: Optimization Of Maintenance Strategy For Critical Medical Eqmentioning
confidence: 99%
“…Mafoud [25] addressed a better part of existing publications on preventive maintenance optimization, particularly applied and validated models in healthcare domain. The study reviewed various important aspects of medical equipment maintenance, analyzes different research insufficiency found in healthcare maintenance optimization modelling literature, and proposed directions to develop suitable tools for better medical devices management.…”
Section: Optimization Of Maintenance Strategy For Critical Medical Eqmentioning
confidence: 99%
“…The process of maintenance must be performed efficiently and effectively because improper maintenance and repairs can lead to unsafe conditions and reduced system performance and availability. Moreover, the cost-factor makes the maintenance strategy challenging because it is believed that 1/3rd of the overall maintenance cost is wasted either due to unnecessary or ineffective maintenance [24,27], and given the large number of such machine, the waste can be significant. Therefore, there is an urge to develop a cost effective maintenance strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, PM is carried out periodically on the basis of experience [41] or from the recommendation of the equipment manufacturers, and it does not account for unexpected failures because their failure mechanisms are time based [8]. PM and CM has been employed for general medical equipment [16,19,23,25] but their implementation lacks simplicity and cost-effectiveness [21,24].…”
Section: Introductionmentioning
confidence: 99%